Influence of obstacle color on locomotor and gaze behaviors during obstacle avoidance in people with Parkinson’s disease - Penedo, Tiago [UNESP]; Polastri, Paula Fávaro [UNESP]; Rodrigues, Sérgio Tosi [UNESP]; Simieli, Lucas [UNESP]; Baptista, André Macari [UNESP]; Moretto, Gabriel Felipe [UNESP]; Imaizumi, Luis Felipe Itikawa [UNESP]; Santinelli, Felipe Balistieri [UNESP]; Barbieri, Fabio Augusto [UNESP] (Springer Nature, 2018)
The color of an obstacle may enable a more detailed view of the environment to facilitate obstacle avoidance. However, people with Parkinson’s disease (PD) present visual contrast and color detection dysfunction, which could affect obstacle avoidance according to obstacle color. Thus, the aim of this study was to investigate the influence of obstacle color on locomotor and gaze behavior during obstacle avoidance in people with PD and neurologically healthy older individuals. Thirteen people with PD and eleven matched-control group individuals, with normal visual acuity (20/20 on the Snellen chart), performed 20 trials (5 trials for each obstacle color condition) of the obstacle avoidance task with the following obstacle colors: white, black, red, and blue. Participants were positioned at the beginning of a walkway with their eyes closed and, after the start command, opened their eyes, started walking at their preferred velocity, and crossed the obstacle. Spatial–temporal parameters and fixations on the obstacle (gaze behavior) were measured using a three-dimensional camera system and mobile eye-tracker, respectively. Our main findings were the absence of significant color interaction on locomotor and gaze behaviors, the absence of significant main effect of color on gaze behavior, and an effect of obstacle color on locomotor behavior, specifically in the placement of the heel from the obstacle after crossing and toe-clearance for both trailing and leading limbs, which indicates that obstacle color can play a role in obstacle avoidance during walking. However, there was no consistent obstacle color that influenced the locomotor behavior. Therefore, the conclusion of this study is that obstacle color seems to affect locomotor behavior, but not gaze behavior, during walking with obstacle avoidance in people with PD and neurologically healthy individuals. However, no particular obstacle color causes a consistent effect on locomotor behavior.
Keywords: Adaptive gait; Color discrimination; Contrast sensitivity; Human movement; Parkinson’s disease; Physical salience